MRX87 family with Aristaless X dup24bp mutation and implication for polyAlanine expansions - Laperuta, Carmela (BioMed Central, 2007)
BACKGROUND: Cognitive impairments are heterogeneous conditions, and it is estimated that 10% may be caused by a defect of mental function genes on the X chromosome. One of those genes is Aristaless related homeobox (ARX) encoding a polyA-rich homeobox transcription factor essential for cerebral patterning and its mutations cause different neurologic disorders. We reported on the clinical and genetic analysis of an Italian family with X-linked mental retardation (XLMR) and intra-familial heterogeneity, and provided insight into its molecular defect. METHODS: We carried out on linkage-candidate gene studies in a new MRX family (MRX87). All coding regions and exon-intron boundaries of ARX gene were analysed by direct sequencing. RESULTS: MRX87 patients had moderate to profound cognition impairment and a combination of minor congenital anomalies. The disease locus, MRX87, was mapped between DXS7104 and DXS1214, placing it in Xp22-p21 interval, a hot spot region for mental handicap. An in frame duplication of 24 bp (ARXdup24) in the second polyAlanine tract (polyA_II) in ARX was identified. CONCLUSION: Our study underlines the role of ARXdup24 as a critical mutational site causing mental retardation linked to Xp22. Phenotypic heterogeneity of MRX87 patients represents a new observation relevant to the functional consequences of polyAlanine expansions enriching the puzzling complexity of ARXdup24-linked diseases.